The Urgency of the Islamic Law and Contemporary Societal Challenges: The Flexibility of al-Maslahah in Determining the Hierarchy of Maqāṣid al-Sharīʿah - Mubarrak, Zahrul; Abu Bakar, Imran; Hamdani, Muslem; Musrizal, Musrizal; Khalilullah, Khalilullah (El-Usrah: Jurnal Hukum Keluarga, 2025)
This study explores the elasticity of the concept of al-maslahah in determining the hierarchy of maqāṣid al-sharīʿah, a critical issue in the development of contemporary Islamic legal thought. The central research question addresses how al-maslahah, as a foundational legal principle, can guide the prioritization within the maqāṣid framework and how its flexibility influences the formulation of the Islamic law in the modern era. This study positions al-maslahah as a key element in the methodology of legal istinbāṭ, facilitating the classification of legal objectives into three primary categories: ḍarūriyyāt (necessities), ḥājiyyāt (needs), and taḥsīniyyāt (embellishments). Employing a normative legal method and a maslahah-based approach, the research conducts a comparative analysis of classical and contemporary scholarly perspectives. The data is drawn from core Islamic legal sources the Qur’an, Hadith, and scholarly writings both supporting and critiquing the concept sourced from authoritative books and peer-reviewed journal articles. The findings reveal that while some variation exists in the formulation of the maqāṣid hierarchy, the majority of scholars continue to adhere to the classical structure established by Imam al-Ghazālī, encompassing five essential protections: religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). However, contemporary scholars such as Jasser Auda and Ali Jumʿah advocate for a more dynamic and contextualized interpretation of this hierarchy to better address present-day challenges. This study underscores that the elasticity of al-maslahah plays a vital role in preserving the relevance of maqāṣid al-sharīʿah, while also stressing the need for clear boundaries to prevent the erosion of sharia’s core principles. In this context, the research affirms the critical role of Islamic law in responding to contemporary societal challenges.